Feasibility and acceptability of the multicontext approach for individuals with acquired brain injury in acute inpatient rehabilitation: A single case series. Issue 2 (7th February 2022) - Jaywant, Abhishek; Steinberg, Chelsea; Lee, Alyson; Toglia, Joan
ABSTRACT: The Multicontext (MC) approach, a metacognitive intervention designed to improve awareness, strategy use, and executive functioning, may be beneficial for individuals with acquired brain injury (ABI) undergoing acute inpatient rehabilitation. The goal of this study was to provide evidence of feasibility and acceptability of the MC approach and to explore clinical outcomes. A case series of eight individuals with acquired brain injury and at least mild executive functioning impairment were recruited from an acute inpatient rehabilitation unit. The MC approach – involving guided questioning and patient self-generation of strategies practiced across everyday functional cognitive tasks – was implemented within routine occupational therapy. Occupational therapists implemented the MC approach with high adherence to the treatment protocol. Therapists' perceived challenges were the time constraints of inpatient rehabilitation as well as client factors. Participants rated the MC approach as highly satisfying and engaging. They described subjective improvements in their ability to use executive functioning strategies. The MC approach was associated with improvement in awareness, strategy use, and executive functioning at the conclusion of treatment. The MC approach may be a beneficial intervention for individuals with acquired brain injury and executive dysfunction undergoing acute inpatient rehabilitation. Further evaluation with larger samples in controlled trials is warranted. Trial registration: ClinicalTrials.gov identifier: NCT04363645. .